Impact of Service Orientation on Financial Performance of Banking Sector of Pakistan: Examining the Mediating Role of Job Satisfaction - Akhtar, Adeel; Mahmood, Zeeshan; Nawaz, Muhammad Kashif; Haider, Muhammad John (2017)
The services sector of an economy plays major role in financial and social development. Services sector is dominant in the developed economies as it contributes upto 70% of total GDP. Even in the case of manufacturers it is difficult to survive without providing quality services. To shed light on the subject, this study aims to find the impact of service orientation on financial performance through mediating role of employees’ job satisfaction in banking sector of Pakistan. For this purpose, data were collected from staff working in the banking sector of district Vehari, Pakistan.Questionnaire was used as a tool for data collection from a sample of 196 employees working in banks of district Vehari.SPSS 17 was used as a tool for data analysis.Findings of factor analysis are used to test the validity of the measured constructs.Cronbach’s alpha confirmed the reliability of the measured constructs. Likewise, correlation and regression analysis show that all the study variables are positively related to each other.More specifically, Service orientation has affirmative and significant impact on the financial performance and employees’ job satisfaction.Furthermore, it is also confirmed that employees’ job satisfaction mediates the relationship between service orientation and financial performance in banking sector of Pakistan. These findings are helpful for the HR policy makers for improvement in the HR policies and resultantly improvement in the financial performance of banks.